2021
DOI: 10.1186/s12893-021-01152-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the conversion rate as it relates to preoperative risk factors and surgeon experience: a retrospective study of 4013 patients undergoing elective laparoscopic cholecystectomy

Abstract: Background Our aim is to determine the relationships among patient demographics, patient history, surgical experience, and conversion rate (CR) during elective laparoscopic cholecystectomies (LCs). Methods We analyzed data from patients who underwent LC surgery between 2005 and 2014 based on patient charts and electronic documentation. CR (%) was evaluated in 4013 patients who underwent elective LC surgery. The relationships between certain predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…The rates of conversion to an alternative surgical technique and 90-day mortality rates were low across all surgical indications. The rates of conversion to open surgery reported in this analysis were lower than those reported elsewhere: a conversion rate of 0.6% for robot-assisted cholecystectomy was slightly lower than a rate of 4.2% reported for laparoscopic cholecystectomy; 16 a conversion rate of 6.9% for robot-assisted anterior resection was lower than that of 29% reported for laparoscopic anterior rectal resection; 17 as was the conversion rate of 0.9% for robot-assisted TLH versus 5.0% reported for laparoscopic hysterocolpectomy 18 . The mortality rates reported in this analysis were also lower than or similar to that reported elsewhere: a 90-day mortality rate of 0.6% for robot-assisted cholecystectomy was comparable to operative mortality of 0.5% described for laparoscopic cholecystectomy; 19 a 90-day mortality rate of 0.0% for robot-assisted anterior resection was lower than that of 2.1% reported for laparoscopic resection; 20 a 90-day mortality rate of 0.0% for robot-assisted TLH was similar to reported operative mortality of 1:6814 for laparoscopic and robotic hysterocolpectomy 21 …”
Section: Discussioncontrasting
confidence: 79%
“…The rates of conversion to an alternative surgical technique and 90-day mortality rates were low across all surgical indications. The rates of conversion to open surgery reported in this analysis were lower than those reported elsewhere: a conversion rate of 0.6% for robot-assisted cholecystectomy was slightly lower than a rate of 4.2% reported for laparoscopic cholecystectomy; 16 a conversion rate of 6.9% for robot-assisted anterior resection was lower than that of 29% reported for laparoscopic anterior rectal resection; 17 as was the conversion rate of 0.9% for robot-assisted TLH versus 5.0% reported for laparoscopic hysterocolpectomy 18 . The mortality rates reported in this analysis were also lower than or similar to that reported elsewhere: a 90-day mortality rate of 0.6% for robot-assisted cholecystectomy was comparable to operative mortality of 0.5% described for laparoscopic cholecystectomy; 19 a 90-day mortality rate of 0.0% for robot-assisted anterior resection was lower than that of 2.1% reported for laparoscopic resection; 20 a 90-day mortality rate of 0.0% for robot-assisted TLH was similar to reported operative mortality of 1:6814 for laparoscopic and robotic hysterocolpectomy 21 …”
Section: Discussioncontrasting
confidence: 79%
“…Several studies, [26][27][28][29] including meta-analyses, 30,31 have been carried out to identify the risk factors of conversion, including patient characteristics, such as sex, comorbidities, history of abdominal surgery and the severity of cholecystitis with the delay of the surgery or gangrene of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…They may be explained by residual confounding related to volume and outcome, or the fact that differences in outcomes after acute surgery are influenced to a greater extent by other factors. Previously published studies [21][22][23][24] have suggested that patient characteristics, such as male sex, age, and previous upper abdominal surgery, or the presence of cholecystitis, have a greater impact on outcomes than the surgeon's operative volume. Although the mortality rate after gallbladder surgery is low, 30-day mortality doubled in hospitals with less extensive volumes.…”
Section: Discussionmentioning
confidence: 99%